'If it makes you feel good it must be right': Embodiment strategies for healthy eating and risk management. Issue 4 (26th June 2013) - Kristensen, Dorthe Brogård; Askegaard, Søren; Jeppesen, Lene Hauge
ABSTRACT The following arguments are constructed around the encounter of embodied experiences and societal discourses. On the basis of an ethnographic study of 34 Danish consumers, we present different consumers' strategies in relation to their perception of healthy food and management of food‐related health risk. Drawing on a subsample representing particular subject positions in relation to healthy eating, we argue for an increased role of embodiment in consumers' risk handling. The study shows that because of the overload of information, consumers increasingly turn to personal experiences and bodily feelings as the instrument and strategy for evaluating possible health risk and benefit. Furthermore, the study shows how these evaluations are related to broader political and socio‐economic issues as well as closely intertwined with notion of trust and mistrust. Through embodied feelings, consumers navigate and negotiate their position in relation to social discourses of health and risk. Copyright © 2013 John Wiley & Sons, Ltd.